Aplikasi Safety Driving Assistance Dengan Perhitungan Haversine: Universitas Pakuan Bogor - Perdi Yansyah perdi; Mohamad Iqbal Suriansyah Iqbal; Arie Qur’ania Arie (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2024)
This research proposes a solution to improve driving safety in Bogor City through the development of an Android-based driving companion application. This application provides a sound warning to drivers when approaching accident-prone locations within a radius of 900 meters. In addition, this application utilizes Location Based Service technology to provide information about the nearest accident-prone locations. The method applied uses the Haversine formula to calculate the distance between the user's location and accident-prone points. The Haversine formula, commonly used to measure the distance between latitude and longitude coordinates, is expected to provide high accuracy calculations. This application aims to provide early warning to drivers, increase awareness, and provide effective information regarding vulnerable locations. With this application, it is hoped that it can reduce the level of traffic accidents in Bogor City. Drivers will be more alert and informed about vulnerable locations, providing early warning when approaching dangerous areas. This solution is expected to contribute positively to driving safety and traffic safety in the region.